Aliran Filsafat Pendidikan Barat - Khumaidi, Ahmad (LP3M UNZAH GENGGONG, 2022)
Since humans want progress in life, since then the idea has arisen to transfer, preserve and develop culture through education. Education in society has always been a major concern in order to advance the lives of generations that are in line with the demands, developments and progress of society from time to time. Considering that the development of life and the implementation of education are dynamic, the ideas that emerge are also dynamic (according to the nature of thought and human dynamics). Conditions ultimately encourage the birth of schools in education. Streams in education need to be mastered by prospective educators because education is not enough to be understood only through a partial and descriptive scientific approach, but also needs to be viewed holistically (overall). According to Tirtarahardja & Sulo (2005) schools of education have started since the beginning of human life, because every human group is always faced with the younger generation of their offspring who need better education from their parents. In the literature on educational streams, ideas about education have started from the ancient Greeks to the present, known as the Islamic and Western Schools of Education. Keywords: Western Educational Western Philosophy